Adsorption of Fe(II) by Layered Double Hydroxide Composite with Carbon-Based Material (Biochar and Graphite): Reusability and Thermodynamic Properties - Neza Rahayu Palapa; Alfan Wijaya; Patimah Mega Syah Bahar Nur Siregar; Amri Amri; Nur Ahmad; Tarmizi Taher; Aldes Lesbani (Indonesian Journal of Chemistry, 2023)
Layered double hydroxide (LDH) of Ni/Al was synthesized by coprecipitation method at pH 10 followed by the formation of composite with carbon-based material i.e., biochar (B) and graphite (G) to form Ni/Al-B and Ni/Al-G. Materials were characterized by XRD powder, FTIR, BET surface area, thermal analyses, and SEM analysis. The regeneration process and adsorption evaluated the performance of materials toward iron(II) [Fe(II)] from an aqueous solution. The results showed that the surface area of Ni/Al-B (428.94 m2/g) was increased mainly up to twenty-nine-fold than Ni/Al LDH (15.11 m2/g), while Ni/Al-G (21.59 m2/g) had slightly increased than pristine LDH. Composite of Ni/Al-B had reusability properties for Fe(II) adsorption up to five cycles and showed higher structural stability. The adsorption capacity of Ni/Al-B was 104.167 mg/g and can be a potential adsorbent to remove Fe(II) from an aqueous solution.